Here's the question you clicked on:
Troublemaker
What is the simplified form of (3x^3 – 4x^2 + 6x) – (5x^3 + 2x^2 – 3x) in standard form?
a.) –3x^3 – 2x^2 + 3x b.) –2x^3 – 6x^2 – 3x c.) –2x^3 – 6x^2 + 9x d.) 8x^3 – 6x^2 – 9x
How'd you get that?
\[(3*x{}^{\wedge}3 - 4*x{}^{\wedge}2 + 6*x) - (5*x{}^{\wedge}3 + 2*x{}^{\wedge}2 - 3*x) \]\[3 x^3 -4 x^2+ 6 x-5 x^3-2 x^2+3 x \]\[3 x^3 -5 x^3- 4 x^2 -2 x^2+ 6 x+3 x \]\[-5 x^3-2 x^2+3 x \]
Very sorry. There is a posting error above. Replace \[-5 x^3-2 x^2+3 x \] with \[-2 x^3-6 x^2+9 x \]